2021
DOI: 10.1155/2021/6655122
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Blood‐Brain Barrier (BBB) Permeability Is Regulated by MMP3 via the ERK Signaling Pathway

Abstract: Background. The blood-brain barrier (BBB) regulates the exchange of molecules between the brain and peripheral blood and is composed primarily of microvascular endothelial cells (BMVECs), which form the lining of cerebral blood vessels and are linked via tight junctions (TJs). The BBB is regulated by components of the extracellular matrix (ECM), and matrix metalloproteinase 3 (MMP3) remodels the ECM’s basal lamina, which forms part of the BBB. Oxidative stress is implicated in activation of MMPs and impaired B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 53 publications
(67 reference statements)
0
30
0
Order By: Relevance
“…This tripeptide promotes VE‐cadherin phosphorylation to enhance vascular permeability in a CXC chemokine receptor 2 (CXCR2) signaling system–dependent manner. ADAM10, 17, and MMP3 degrade junction proteins 12‐14 . Angiomodulin produced in human bladder carcinoma cells and fibroblasts binds integrin ανβ3 to induce actin stress fibers, resulting in loosening of the VE‐cadherin–mediated intercellular junctions 15 .…”
Section: Vascular Permeability Factors (Vpfs)mentioning
confidence: 99%
See 3 more Smart Citations
“…This tripeptide promotes VE‐cadherin phosphorylation to enhance vascular permeability in a CXC chemokine receptor 2 (CXCR2) signaling system–dependent manner. ADAM10, 17, and MMP3 degrade junction proteins 12‐14 . Angiomodulin produced in human bladder carcinoma cells and fibroblasts binds integrin ανβ3 to induce actin stress fibers, resulting in loosening of the VE‐cadherin–mediated intercellular junctions 15 .…”
Section: Vascular Permeability Factors (Vpfs)mentioning
confidence: 99%
“…These enzymes are produced as proenzymes and later processed by other proteases to make active forms. Active enzymes can degrade junction proteins to reduce cell‐cell contact and increase vascular permeability 12‐14 Permeability factors downregulate expression of genes encoding junction proteins (Figure 1A‐3).…”
Section: Mechanisms Of Action Of Permeability Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…MMP3 is a member of the MMP family, which is widely involved in the breakdown of extracellular matrix proteins during tissue remodeling, such as embryonic development and reproduction, as well as in disease processes, such as arthritis and tumor metastasis [47]. MMP3 can degrade collagen, elastin, fibronectin, laminin, as well as tight junctions, so as to increase vascular permeability and disrupt the BBB [25,41,48,49]. In hBMECs, our results suggested that lncRSPH9-4 was able to regulate MMP3 expression by acting as a competitive sponge of miR-17-5p.…”
Section: Discussionmentioning
confidence: 99%